2017
DOI: 10.1088/1478-3975/13/6/066013
|View full text |Cite
|
Sign up to set email alerts
|

A better prediction of conformational changes of proteins using minimally connected network models

Abstract: Elastic network models have recently been used for studying low-frequency collective motions of proteins. These models simplify the complexity that arises from normal mode analysis by considering a simplified potential involving a few parameters. Two common parameters in most of the elastic network models are cutoff radius and force constant. Although the latter has been studied extensively and even elaborate new models were introduced, for the former usually an ad-hoc cutoff radius is considered. Moreover, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In the past decades, a large number of studies have shown the usefulness of NMA and Principal Component Analysis (PCA) for the prediction and analysis of protein co-operative motions [ 13 , 14 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Many of these studies were conducted using computationally simple ENM that use uniform harmonic potentials for interacting atom (or residue) pairs instead of more complicated potentials.…”
Section: Coarse-grained Protein Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, a large number of studies have shown the usefulness of NMA and Principal Component Analysis (PCA) for the prediction and analysis of protein co-operative motions [ 13 , 14 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Many of these studies were conducted using computationally simple ENM that use uniform harmonic potentials for interacting atom (or residue) pairs instead of more complicated potentials.…”
Section: Coarse-grained Protein Modelingmentioning
confidence: 99%
“…Except as mentioned above, ENMs have been successfully used in many combinations with different input information and methods, such as, for example, data from electron microscopy [ 14 ], atomistic MD simulations [ 17 , 77 ], Brownian simulations [ 78 ], structure-based models [ 79 , 80 ], and many other combinations that have been thoroughly reviewed [ 13 , 14 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ].…”
Section: Coarse-grained Protein Modelingmentioning
confidence: 99%
“…In the last decades, a large number of studies have shown the usefulness of Normal Mode Analysis (NMA) and Principal Component Analysis (PCA) for the prediction and analysis of protein cooperative motions [13,14,[54][55][56][57][58][59][60][61][62][63]. Many of these studies were conducted using computationally simple Elastic Network Models (ENM) which use uniform harmonic potentials for interacting atom (or residue) pairs instead of more complicated potentials.…”
Section: Elastic Network Modelsmentioning
confidence: 99%
“…Except as mentioned above, ENMs have been successfully used in many combinations with different input information and methods, such as for example data from electron microscopy [14], atomistic MD simulations [17,78], Brownian simulations [79], structure-based models [80,81] and many other combinations that have been thoroughly reviewed [13,14,[54][55][56][57][58][59][60][61][62][63]. When the range of protein structural dynamics studies can be limited to a roughly defined vicinity of a specific folded structure (determined by experiment), ENM, CG models or their modifications can be very effective in predicting protein flexibility [8,36,[82][83][84].…”
Section: Elastic Network Modelsmentioning
confidence: 99%
“…We focus on advancing PSN analysis from three new aspects. First, we examine whether network analysis results can discriminate between subtle (yet significantly different function-wise) protein conformations [45] , [46] , [47] . This perspective has not been extensively explored previously.…”
Section: Introductionmentioning
confidence: 99%